Ngữ pháp tiếng Anh thực hành : có phần bài tập và đáp án - Thomson, A. J. (Nxb Tp.HCM, 1996)
Articles and one, a little / a few, this, that; Nouns; Adjectives; Adverbs; All, each, every, both, neither, either, some, any, no, none; Interrogatives; Possessives, personal and reflexive pronouns: my, mine, I, myself, etc...